Pengembangan Sistem Informasi Rekam Medis untuk Dinas Kabupaten Grobogan - Purnaresa Yuliartanto; Adian Fatchur Rochim; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
Abstract - Health services include the recording of the patient's medical record . Medical records were used to aid the treatment process. The number of medical records continues to grow proportional to the number of patients. Tens of thousands of sheets of paper used to record medical record requires effort , time and place great . The amount of effort will continue to grow each day. Search one sheet of medical records among a set of storage shelves requires considerable time and risk data is not found. The risk of error in the search and storing will increase every day. The development of technology allows the implementation of technology in the process of record-keeping. Changes in the form of digital medical records will reduce the need of a previous process. Labor, time and place required by the help of information systems will be reduced significantly . Storage process data stored in the cloud will provide more value for the system as a patient's medical records from a health center can be accessed from other health centers. The development of this system will reduce the risk of inappropriate storage and retrieval of medical records. Grobogan Health Department that oversees health center in Grobogan are office that are ready to migrate business processes into the digital age. Development of medical record information system for the health center expected to improve the quality of service of health centers , especially in health care.